The relationship between depression and executive function and the impact of vascular disease burden in younger and older adults - Lugtenburg, Astrid; Oude Voshaar, Richard C.; Van Zelst, Willeke; Schoevers, Robert A.; Enriquez-Geppert, Stefanie; Zuidersma, Marij (Age and ageing, 2017)
depression is associated with worse executive function, but underlying mechanisms might differ by age. to investigate whether vascular disease burden affects the association between depression and executive dysfunction differentially by age. among 83,613 participants of Lifelines (population-based cohort study), linear regression analyses were applied to examine the association between executive function (Ruff Figural Fluency test, dependent variable) and depression according to DSM-IV criteria (Mini International Neuropsychiatric Interview, independent variable). adjusted for demographic characteristics, major depressive disorder was associated with a lower level of executive function in both younger and older adults. Minor depressive disorder was only associated with worse executive function in younger adults. Adding vascular disease burden to the final model with major depressive disorder, reduced this strength of this association by 5.9% in younger and 5.0% in older adults. major depression was associated with worse executive function across the lifespan, but minor depression only in younger adults. The impact of vascular burden on the association did not differ between younger and older adults. Therefore, vascular risk reduction is important in both age groups.